Enhancing Modern Chinese Literature Learning: A Quasi-Experimental Study of the Superstar Learning Platform's Impact - Zeng, Kuifen; Li, Changhan (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: The integration of digital platforms in education enhances teaching and learning. This study evaluated the Superstar Learning Platform's effectiveness as a supplementary tool for Modern Chinese Literature (MCL), aiming to address the shortcomings of traditional methods, such as a lack of comprehensiveness and student engagement. The goal is to assess its effectiveness on reading competence, literary appreciation, student performance, and total scores. Materials and Methods: A quasi-experimental design involving 95 undergraduates assessed the Superstar Learning Platform's impact on reading competence, literary appreciation, performance, and total scores. Fifty students used the platform (experimental group), while 45 received traditional teaching (control group). Quantitative data were gathered through the design, and qualitative data were collected via an open-ended questionnaire to explore the experimental group's satisfaction with MCL. Results: Quantitative data showed that the experimental group achieved significantly greater improvements than the control group. Notable mean improvements were observed in reading competence (11.6 vs. 2.49), literary appreciation (4.48 vs. 2.38), student performance (4.02 vs. 1.12), and total scores (7.9 vs. 2.12), demonstrating the effectiveness of the intervention of Superstar Learning Platform. Qualitative feedback confirmed that most experimental group students expressed positive attitudes toward the Superstar Learning Platform. Conclusion: This study demonstrated that with the platform, the experimental group achieved significant improvements in reading competence, literary appreciation, student performance, and total scores compared to the control group. Furthermore, a majority of the experimental group held positive attitudes towards the platform. It indicated that the implementation of the Superstar Learning Platform in MCL had notable effects.